The GLEAM 4-Jy (G4Jy) Sample: I. Definition and the catalogue. (2020) - White, Sarah V.; Franzen, Thomas M. O; Riseley, Chris J.; Wong, O. Ivy; Kapińska, Anna D.; Hurley-Walker, Natasha; Callingham, Joseph R.; Thorat, Kshitij; Wu, Chen; Hancock, Paul; Hunstead, Richard W.; Seymour, Nick; et al.
Abstract: The Murchison Widefield Array (MWA) has observed the entire southern sky (Declination, δ< 30^° ) at low radio frequencies, over the range 72–231MHz. These observations constitute the GaLactic and Extragalactic All-sky MWA (GLEAM) Survey, and we use the extragalactic catalogue (EGC) (Galactic latitude, |b| >10^° ) to define the GLEAM 4-Jy (G4Jy) Sample. This is a complete sample of the 'brightest' radio sources ( S_151 MHz>4 Jy ), the majority of which are active galactic nuclei with powerful radio jets. Crucially, low-frequency observations allow the selection of such sources in an orientation-independent way (i.e. minimising the bias caused by Doppler boosting, inherent in high-frequency surveys). We then use higher-resolution radio images, and information at other wavelengths, to morphologically classify the brightest components in GLEAM. We also conduct cross-checks against the literature and perform internal matching, in order to improve sample completeness (which is estimated to be >95.5 %). This results in a catalogue of 1863 sources, making the G4Jy Sample over 10 times larger than that of the revised Third Cambridge Catalogue of Radio Sources (3CRR; S_178 MHz>10.9 Jy ). Of these G4Jy sources, 78 are resolved by the MWA (Phase-I) synthesised beam ( 2 arcmin at 200MHz), and we label 67% of the sample as 'single', 26% as 'double', 4% as 'triple', and 3% as having 'complex' morphology at 1 GHz (45 arcsec resolution). We characterise the spectral behaviour of these objects in the radio and find that the median spectral index is α=-0.740 ± 0.012 between 151 and 843MHz, and α=-0.786 ± 0.006 between 151MHz and 1400MHz (assuming a power-law description, S_ν ν^α ), compared to α=-0.829 ± 0.006 within the GLEAM band. Alongside this, our value-added catalogue provides mid-infrared source associations (subject to 6" resolution at 3.4 μ m) for the radio emission, as identified through visual inspection and thorough checks against the literature. As such, the G4Jy Sample can be used as a reliable training set for cross-identification via machine-learning algorithms. We also estimate the angular size of the sources, based on their associated components at 1 GHz, and perform a flux density comparison for 67 G4Jy sources that overlap with 3CRR. Analysis of multi-wavelength data, and spectral curvature between 72MHz and 20GHz, will be presented in subsequent papers, and details for accessing all G4Jy overlays are provided at https://github.com/svw26/G4Jy .